Perlindungan Hak atas Tempat Tinggal yang Layak bagi Warga Terdampak Penggusuran - Wahyuni, Ridha (Jurnal Indonesia Sosial Sains, 2022)
Evictions are still one of the methods used by the government in the context of land acquisition for development, especially for people who do not have land ownership rights documents but residents have controlled the land as land for residence for a long time. Protection of the right to adequate housing is one of the human rights that must be protected, because this right is also related to guaranteeing the sustainability of human life. This study focuses on the issue of the impact of evictions on the protection of the right to adequate housing for residents in RT/RW 03/03 Batu Ceper, Tangerang as residents affected by eviction due to development. Examining the responsibility of the Tangerang City government in providing protection to guarantee the survival of the affected residents through the provision of adequate housing. The research method used is juridical-empirical. The results showed that the Tangerang City Government provided Rusunawa to affected residents for relocation but the residents refused, this is because the appointment of the Rusunawa was done unilaterally by the government so that they still did not pay attention to the standards for providing adequate housing according to human rights standards consisting of aspects of availability, aspects of affordability of costs and aspects of location. Therefore, it is hoped that the local government before carrying out an eviction needs to involve the participation of the affected community to identify the needs of the residents regarding the fulfillment of replacement housing in order to ensure the protection of the survival of the residents after they have been evicted.